Comparison of a laboratory-scale coke and a pilot-scale coke from matched coal. (28th May 2021) - Lomas, Hannah; Roest, Richard; Wells, Adam; Thorley, Tizshauna; Wu, Hui; Jiang, Zhengyi; Sakurovs, Richard; Fetscher, Robert; Xing, Xing; Mahoney, Merrick R.
ABSTRACT: A coke produced using a custom-built sole-heated oven and a coke prepared in a pilot-scale oven from a matched coal, were compared using a range of analytical techniques. The aim of this comparison was to assess to what extent the small-scale sole-heated oven can successfully replicate the production of pilot-scale oven cokes, and thus be used to rapidly prepare and screen a wide range of cokes for particular characteristics, e.g. abrasion resistance. The techniques applied included conventional methods and novel methods developed by our research team. These included microstructural and microtextural analyses of samples of each coke, and tribological, scratch test and fractographic analyses, each of which elucidates different strength attributes. These include microstructural weaknesses, abrasion resistance, and the strength of microtextural interfaces. The level of replication achieved indicates that the sole-heated oven, used in combination with an annealing step in a muffle furnace, can be beneficially used to model the pilot-scale oven.